Mengenal Anak Berkebutuhan Khusus dan Klasifikasinya - Mardiansah Mardiansah; Rizki Alvi Ramadhan; Reni Suryani (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This article aims to describe getting to know children with special needs and their classification. This research uses a qualitative descriptive research method. Data collection techniques include: observation, interviews, and documentation. The research subjects or informants are parents, the community, class teachers/homeroom teachers and special guidance teachers. The results of the research show that: children with special needs are children who experience significant abnormalities or deviations (physical, mental, intellectual, social and emotional) in the process of their growth and development compared to other children of the same age and therefore require special education services. Children with special needs have different characteristics from one another. The characteristics and obstacles they have, ABK require special forms of education services that are tailored to their abilities and potential. The classification of children with special needs is divided into several groups, including: blind, mentally retarded, deaf, physically disabled, hearing impaired, learning difficulties, cerebral palsy, autism, gifted children, rett's disorder, Asperger's, slow learners, and ADHD.